Autonomy vs. Societal Pressures: The Dilemma of Independent Women in Modern Society - Muhammad Fakhran al Ramadhan (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study examines the experiences and challenges faced by independent women in Indonesia within the context of education, societal roles, and gender expectations. The research addresses issues of autonomy, societal pressures, and the impact of education on women’s empowerment. Using a descriptive qualitative phenomenological approach, data were collected through semi-structured interviews with three women from diverse backgrounds—a university lecturer, a single mother, and a university student. Findings reveal that while these women define independence as control over personal and professional decisions, they encounter significant societal pressures tied to traditional expectations, such as marriage, motherhood, and conformity to conventional gender roles. Each participant negotiates her autonomy by balancing personal ambitions with societal expectations, often at considerable psychological cost, including experiences of frustration, isolation, and self-doubt. Interpreted through Simone de Beauvoir’s existentialist feminist framework—particularly her concepts of immanence, transcendence, and the Other—the study highlights the resilience of Indonesian women in asserting independence despite cultural constraints, while underscoring the continuing need for policy interventions that promote educational access, economic opportunity, and cultural transformation. This research contributes to understanding the complexities of gender equality and the evolving roles of women in contemporary Indonesian society, with particular attention to the gap between formal rights and lived experience.